2022
DOI: 10.5530/097484900254
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Elusive Healer Plant “Luffa echinata Roxb.”

Abstract: Recent years have seen a global rise in the use of herbal medicine. Many naturally occurring bioactive substances, especially those derived from plants, have been studied as potential cures for various diseases. Luffa echinata Roxb., a mysterious medicinal plant from the Cucurbitaceae family, has recently gained recognition as one of the most important medicinal herbs among them. Many phytochemicals found in this plant have been found to have therapeutic potential, including xanthones, alkaloids, phytosterols,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The presence of hexavalent chromiumin in cell generate ROS and cause oxidative stress, leading to cell death (Monga et al, 2022). Bacosides present in B. monnieri, particularly Bacoside A modulate neurotransmitter levels and can enhance synaptic transmission, improving cognitive functions and can even repair neuronal damage by augmenting kinase activity, neuronal synthesis, restoration of synaptic activity and nerve impulse transmission (Mondal et al, 2023). The locomotor dysfunctions were ameliorated in the present study, when the flies In the present study, Bacopa extract showed a better reduction of lipid peroxidation than Moringa extract, which might be due to the presence of higher concentrations of antioxidants in Bacopa, leading to a more significant reduction in lipid peroxidation, suggestive of its more effective antioxidant mechanisms.…”
Section: Total Polyphenol Contentmentioning
confidence: 99%
“…The presence of hexavalent chromiumin in cell generate ROS and cause oxidative stress, leading to cell death (Monga et al, 2022). Bacosides present in B. monnieri, particularly Bacoside A modulate neurotransmitter levels and can enhance synaptic transmission, improving cognitive functions and can even repair neuronal damage by augmenting kinase activity, neuronal synthesis, restoration of synaptic activity and nerve impulse transmission (Mondal et al, 2023). The locomotor dysfunctions were ameliorated in the present study, when the flies In the present study, Bacopa extract showed a better reduction of lipid peroxidation than Moringa extract, which might be due to the presence of higher concentrations of antioxidants in Bacopa, leading to a more significant reduction in lipid peroxidation, suggestive of its more effective antioxidant mechanisms.…”
Section: Total Polyphenol Contentmentioning
confidence: 99%
“…Genus Bacopa contains more than 100 plant species of aquatic herbs, distributed throughout the warmer regions of the world. The details of the taxonomic position with synonyms [18][19][20] of B. monnieri are listed in Table 1 [2,3] and vernacular names are depicted in Table 2. [1,3]…”
Section: Taxonomic Position Synonyms and Vernacular Namesmentioning
confidence: 99%
“…The study of plants (plant taxonomy and study of medicinal plants) may have arisen during this contemporary age, based on the aforementioned historical eras of recording in India from ancient documents and literature. [2]…”
Section: Introductionmentioning
confidence: 99%
“…L. aegyptica) and L. acutangula, are widely grown for their edible fruit and sponge-like fibers, whereas L. echinata and L. graveolens are wild species and known as bitter Luffa. Wild Luffa are having rough texture fruit with a very bitter flavor which are native to South Asia and Southeast Asia and grows abundantly in India, Bangladesh, Pakistan and Northern Tropical Africa with Gujarat, Bihar, Rajasthan and Madhya Pradesh being the most common locations in India (Mondal et al, 2022). Wild Luffa species are used in traditional Ayurvedic medicines, as they have various medicinal properties such as analgesic, laxative, antidepressant, anti-inflammatory, anxiolytic, antibacterial, antifungal, antiepileptic, hepatoprotective, antiulcer, anticancer, anti-anthelminthic and anti-hepatic, hence used to treat bronchitis, piles, jaundice and vaginal discharge (Prakash et al, 2013).…”
Section: Introductionmentioning
confidence: 99%